2012
DOI: 10.1002/app.37921
|View full text |Cite
|
Sign up to set email alerts
|

Biolignin™ based epoxy resins

Abstract: Wheat straw Biolignin TM was used as a substitute of bisphenol-A in epoxy resin. Synthesis was carried out in alkaline aqueous media using polyethyleneglycol diglycidyl ether (PEGDGE) as epoxide agent. Structural study of Biolignin TM and PEGDGE was performed by solid-state 13 C NMR and gel permeation chromatography, respectively, before epoxy resin synthesis. Biolignin TM based epoxy resins were obtained with different ratios of Biolignin TM : PEGDGE and their structures were analyzed by solid-state 13 C NMR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…This result shows that there are as many carboxylic groups in wheat straw lignin as phenolic groups. 20 The presence of carboxylic group may be interesting for other chemical reaction based on lignin. Figure 9 Results obtained of acetylated wheat straw lignin GPC analysis in THF.…”
Section: 23mentioning
confidence: 99%
See 2 more Smart Citations
“…This result shows that there are as many carboxylic groups in wheat straw lignin as phenolic groups. 20 The presence of carboxylic group may be interesting for other chemical reaction based on lignin. Figure 9 Results obtained of acetylated wheat straw lignin GPC analysis in THF.…”
Section: 23mentioning
confidence: 99%
“…Figure 9 Results obtained of acetylated wheat straw lignin GPC analysis in THF. 20 Proposed structures of CIMV wheat straw lignin's fragments…”
Section: 23mentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that organosolv lignin [143][144][145][146] and kraft lignin [147][148][149] could be modified upon reaction with several epoxylated polyethylene glycol (PEG) derivatives. To reduce the cost of preparation, the modification was also carried out using kraft cooking black liquors, since the alkali species were retained and acted as catalysts [149].…”
Section: Etherificationmentioning
confidence: 99%
“…Blending with thermoset and thermoplastic polymer constitutes another opportunity for further conversion of lignin into valuable products. Examples are reported of the use of lignin in copolymers doped by carbon nanotubes for chemical sensors applications [18] or to substitute bisphenol-A in epoxy resin [19]. The scientific literature reports a number of studies dealing with the evaluation of the effect of lignin in the blend with polyvinylacetate [20], polyethylene and polypropylene [21,22].…”
Section: Introductionmentioning
confidence: 98%